Application of Ultrasonic Waves as Pre-Treatment in the Extraction of Essential Oil from Basil Leaves (Ocimum Basilicum) Using Ultrasound-Microwave-Assisted Extraction (UMAE) - Muhammad Taufiq Qurrokhman; Aynia Ayu Nur Afifah; Nove Kartika Erliyanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study investigated the effects of temperature and ultrasonic duration on the Ultrasound–Microwave Assisted Extraction (U-MAE) method for basil leaf essential oil. Key characteristics analysed included yield, density, refractive index, and colour, with results compared to commercial essential oil. The procedure involved drying basil leaves, applying ultrasonic pretreatment at 30- 70 °C for 5-60 minutes, and performing microwave-assisted extraction at 450 W for 30 minutes. Findings indicated that both temperature and ultrasonic duration significantly influenced essential oil characteristics. Optimal conditions were achieved at 50 °C and 30 minutes, resulting in a yield of 2.5551%, a density of 0.9542 g/ml, a refractive index of 1.4960, and a pale yellow color consistent with commercial standards. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production